The Influence of Perceived Security and Perceived Enjoyment on Intention To Use with Attitude Towards Use as Intervening Variable on Mobile Payment Customer in Surabaya - Sudono, Fabrianne Setiawati; Adiwijaya, Michael; Siagian, Hotlan (Petra International Journal of Business Studies, 2020)
This study aims to determine the effect of perceived security and perceived enjoyment as moderated variable on intention to use mobile payment, either directly or through mediation of attitude towards use. The method used in this study is quantitative by spreading the questionnaires to 211 respondents of mobile payment application users both online and offline in Surabaya. The selection of this research sample used a judgment sampling technique with criteria determined by the researcher. The data was analyzed with Structural Equation Modeling (SEM), SmartPLS tools. The questionnaire collected was 192 questionnaires. The results show that perceived security and perceived enjoyment have a significant directly influence on intention to use and indirectly through mediating attitudes to use mobile payment. In addition, it was found that perceived enjoyment variable moderated the relationship between perceived security and attitudes to use but did not moderate the relationship between perceived security and intention to use.